2014
DOI: 10.1155/2014/508231
|View full text |Cite
|
Sign up to set email alerts
|

Mandibuloacral Dysplasia Caused byLMNAMutations and Uniparental Disomy

Abstract: Mandibuloacral dysplasia (MAD) is a rare autosomal recessive disorder characterized by postnatal growth retardation, craniofacial anomalies, skeletal malformations, and mottled cutaneous pigmentation. Hutchinson-Gilford Progeria Syndrome (HGPS) is characterized by the clinical features of accelerated aging in childhood. Both MAD and HGPS can be caused by mutations in the LMNA gene. In this study, we describe a 2-year-old boy with overlapping features of MAD and HGPS. Mutation analysis of the LMNA gene revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…It consists of globular head domain, linker regions, α-helical coiled coil domain and globular tail domain. Locations of the progeria LMNA mutations in this study were shown with molecular mechanism of mutant lamin A protein and clinical phenotype, as previously reported in [ 34 ] (p.Met540Thr) [ 29 ], (c.1824C>T) [ 30 ], (c.1968+1G>A) [ 31 ], (c.1968+2T>C), and [ 36 ] (c.2968G>A and c.1968+5G>A). Δ50 indicates the region of deletion in progerin, also present in ZMPSTE24 mutant progeria [ 32 ].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…It consists of globular head domain, linker regions, α-helical coiled coil domain and globular tail domain. Locations of the progeria LMNA mutations in this study were shown with molecular mechanism of mutant lamin A protein and clinical phenotype, as previously reported in [ 34 ] (p.Met540Thr) [ 29 ], (c.1824C>T) [ 30 ], (c.1968+1G>A) [ 31 ], (c.1968+2T>C), and [ 36 ] (c.2968G>A and c.1968+5G>A). Δ50 indicates the region of deletion in progerin, also present in ZMPSTE24 mutant progeria [ 32 ].…”
Section: Resultssupporting
confidence: 86%
“…Biallelic ZMPSTE24 mutations also cause accumulations of farnesylated lamin A and a varying degree of progeroid phenotypes, depending on the residual enzymatic activity of ZMPSTE24 [ 32 , 33 ]. In rare instances, a homozygous amino acid substitution of lamin A can present with a phenotype similar to HGPS or mandibuloacral dysplasia, as described in cases with [p.Met540Thr; p.Met540Thr] [ 34 ] and [p.Thr528Met; p.Met540Thr] [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…This attribute is distinct from intra‐sutural bones that are juxta‐sutural, and in sharp contrast with the normal appearance of the surrounding parietal bones. Wormian bones have been reported (but not illustrated) in patients with MADA [Shen et al, ; Bai et al, ] but failure of ossification of occipital bone was not mentioned. Wormian bones were also mentioned in three patients with MADB, but only illustrated once [Miyoshi et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Plasilova et al (2004) reported four MADB patients with a homozygous K542N (1626 G > C) mutation in the LMNA gene and this mutation is associated with more severe progeroid features. Another MADB patient with a compound heterozygous R471C/R527C mutation in the LMNA gene was reported by Cao and Hegele (2003) and a homozygous M540T mutation in the LMNA gene by Bai et al (2014).…”
Section: Resultsmentioning
confidence: 99%